# Tag Info

## Hot answers tagged random-walk

3

If I'm not missing something: conditioned on $W_u$, the random variable $W_s - W_u$ is independent with distribution $\mathcal{N}(0, s - u)$. Therefore you can compute the expectation by rewriting $2W_s = 2(W_s - W_u) + 2W_u$: $$\mathbf{E}[2 W_s + W_u | W_u=2] = \mathbf{E}[2(W_s - W_u) + 3W_u |W_u=2] = \mathbf{E}[2(W_s - W_u) | W_u] + 6 =6.$$ Edit: if $... 3 Assume WLOG$A=0$,$B=1$, so that we are inside the interval$[0,1]$, then $$x_{n+1}=\begin{cases} \frac{x_{n}}{2} & p=\frac12\\ \frac12 +\frac{x_{n}}{2} & p=\frac12\\ \end{cases}$$ with$x_0=1/2$. Consider the fractional part of the binary representation of$x_n$. The above transition rule corresponds to shifting the fractional part one place to ... 2 In a Markov chain with limiting distribution$\vec{\pi}$, it takes$\frac1{\pi_i}$expected time to return to state$i$starting from that state. So it's enough to compute the limiting distribution of this Markov chain. Rather than have reflective barriers at$-\frac n2$and$\frac n2$, it is equivalent to make the Markov chain periodic modulo$n$, so that ... 1 One approach - I don't know if it's the intended one - is to replace the simple random walk by another irreducible and recurrent Markov chain. For this problem, let's take the state space to be$\{0,1,2,\dots\}$where states$\{1,2,\dots\}$act like the simple random walk on$\mathbb Z$, but state$0$transitions to state$k$with probability$1$. We can ... 1 About the inequality,$||\mu_n-\mu_n^\prime||_{TV}\leq 2\mathbb{\hat{P}}(T>n)$, it's a bit more involved since by the given definition$T$is not the coupling time of$S$and$S^\prime$(coupling time$\tau=\min\{n\geq 0:S_m=S_m^\prime\text{ for all } m\geq n\}$) . As you have correctly said$||\mu_n-\mu_n^\prime||_{TV}\leq 2\mathbb{\hat{P}}(S_n\neq S_n^\...

1

We don't need to do anything as exotic as Ising models here. Just let $G$ consist of two complete graphs $K_t$ with some bridges between them: In this example with $t=5$, $H$ is the graph on vertex set $\{a,b,c,d,e,f\}$ we get by forgetting the indices on the vertices of $G$; we do the same thing for general $t$. Then $h(G) = \frac2{t+1}$ is achieved by ...

Only top voted, non community-wiki answers of a minimum length are eligible